Phylogenetic Analysis of Elaeagnus L. in China: A Basis for Genetic Improvement of a Berry Crop - Cheng, Chunsong; Fan, Siqing; Wang, Canjian; Ye, Linlin; Wang, Zupeng; Huang, Hongwen (Frontiers in Plant Science, 2022)
Elaeagnus L. is found wild or grown as ornamental plants, and is increasingly regarded as underutilized berry-shrubs by breeders. This genus has cosmopolitan distribution with various species widely distributed in China, Europe, the United States and Canada. Interspecific hybrids, which have been reported several times, have attracted intense interest of plant breeders attempting to develop a fruit crop of Elaeagnus. Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA) is a powerful statistical modeling tool that provides insight into separations between experimental groups. In this study, molecular phylogeny of Elaeagnus species was first discussed using ITS and matK sequences for guiding the construction of genetic basis pool. A mor-phological OPLS-DA clustering model based on the genetic divergence was also constructed for the first time, which effectively realized the morphological grouping of Chinese Elaeagnus species. The results showed that a total of 10 wild species widely distributed in China have potential to develop fruit crops. Particularly, E. conferta has the potential to provide a founder species with large fruit size, while E. Gonyanthes has the potential to provide important genetic resources with long pedicel. E. lanceolata and E. delavayi could be used to domesticate hybrids without spines, and the other five climbing shrubs could be used to develop high-yield crown type commercial cultivars for automated field management. The top five contributing morphological traits affecting the current clustering model were V9 (flower color), V1 (flowering), V5 (evergreen or deciduous), V3 (leaf size) and V2 (fruiting), respectively. Furthermore, the grouping analysis indicated that the V9 was the most important factor affecting the morphological clustering. Thereafter, the temporally calibrated phylogeny inferred from the matK sequence was used to recon-struct the origin and evolution of genus Elaeagnus, and the results inferred an interesting geographic distribution pattern and potential cross-species interactions of Elaeagnus species at low latitudes in China. Our work also highlighted dispersal pattern investigation and genetic background analysis to improve future practices and policies related to species introduction of genetic basis pools.